Aesthetic Transformation of Morsal (Simple) Prose Texts with an Emphasis upon Semantics - Mohsen Vesaghati Jalal (مطالعات زبانی و بلاغی)
To fulfill aesthetic goals, two approaches have been employed in Persian prose works; the first approach is to dress up the exterior of language, while in the second approach, the innermost of the language is embellished by semantics. Stylistic studies of Morsal prose texts revealed that the aesthetic aspects of such works rely on the content of language, within which syntactic elements act as a rhetorical device and give the works aesthetic value. The function of devices in Morsal prose varies because the aesthetic function of  semantics have been altered by time as an influential variable.The objective of this article is to measure the extent of such aesthetic metamorphosis in the field of the semantic in Morsal prose. To achieve this, first, four works: the introduction to Abu Mansouri’s Shahnameh, Tarikh-i Bal'ami or Tārīkhnāma, Tarikh-i Sistan (History of Sistan) and Nowruznameh (Epistle of Nowruz) have been studied through a descriptive-analytical method based on structural stylistics. Then, to show the trajectory of Persian prose evolution, the syntactic rhetorical components of the four works have been compared. The findings of this study indicate that early Persian prose is characterized by semantic components such as sentence structure diversity, brevity, and concision. With the passage of time, however, the exterior of the language has been ornamented by literary elements in a way that Persian prose has significantly changed and a more technical form of prose has emerged.Inspection of the aesthetic evolution of Morsal prose in the field of semantics, illustrates that the “syntactic capabilities” have affected the innermost of language and have fulfilled the literal aspect of the texts by a pleasant blend of novel expression and semantics. The linguistic emancipation resulting from social, political and cultural conditions has also strengthened the syntactic structure. This study displays that the writers of Morsal prose have made the most of the initial and final position of the sentence to create a diverse syntactic structure and secondary meanings; however, this syntactic capability has diminished over time which caused the sentences structure to become monotonous. Another rhetorical component which its transformation has caused great linguistic alterations, is the “length of the sentence”. Over time the increasing length of the sentences in Farsi prose has fetched the elegance of prose to the exterior of the language. The third component is brevity. In the Morsal prose, brevity has helped to create beauty in two ways. The fourth component is the syntactic function of verbs. A variety of prefixed verbs, simple verbs and compound verbs have been used in Morsal's prose, but over time, the frequency of prefixed and suffixed verbs has decreased and the language has become tense and sedentary.Another rhetorically convenient, syntactic component regarding Morsal prose are the various types of "Vav". In Morsal's prose, the usage of the initial and linking "Vav" leads to: brevity, secondary implications, prose rhythm and elegance. In such prose initial "Vav" and linking "Vav" (between sentences), were of more salience, but over time their frequency has decreased meanwhile the number of linking "Vav" (between words) has added on. This kind of syntactic changes, gradually remodel Morsal's prose towards technical prose, and the elements of beauty have shifted from the innermost to the exterior of the language.